Bioaccumulation of Cadmium in Channa striata Fish from the Miai River, Banjarmasin, South Kalimantan - Nurhilaliyyah Nurhilaliyyah; Heri Budi Santoso; Muhamat Muhamat; Hameda Dhaka Kusuma Taufiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Miai River in Banjarmasin is a habitat for the snakehead fish (Channa striata) located in a densely populated area with high human activity, potentially polluted by heavy metals such as cadmium. This study is important to monitor heavy metal concentration & their risks to the health & sustainability of the river ecosystem. The method used was purposive sampling with samples in the form of river water & snakehead fish (C. striata) at two different stations. Heavy metal analysis used Atomic Absorption Spectrophotometry (AAS). The results showed that kadmium concentration in water & fish at both stations were still safe or below the established quality st&ards. There was a significant negative correlation between the two (r=-0.472) & between cadmium concentration in fish & fish weight (r:-0.424). The conclusion of this study is that cadmium concentration in water can reduce fish quality & potentially pose a health risk to humans. The implications of this study emphasize the need for routine monitoring & preventive measures for heavy metal contamination.